Gestación y enfermedad renal crónica en hemodiálisis en una ciudad de altura - Arellán-Bravo, Luis (2023)
A 39-year-old woman, residing at 3,200 meters above sea level, with stage 5 chronic kidney disease and on hemodialysis, who presented an unscheduled pregnancy. During gestation, she was on daily hemodialysis regimen with 21 hours per week, restricted heparin, multidisciplinary management, in addition to high doses of erythropoietin reaching 16,000 IU weekly. At 32 weeks of gestation she underwent emergency cesarean section due to intrauterine growth restriction type III. A male newborn was born APGAR 8-9, weight 1,420 grams, who was transferred to the neonatal intensive care unit. After 30 days, the newborn was discharged, and the mother had a stable and uncomplicated puerperium. This is the first case reported in a pregnant hemodialysis patientliving at high altitude. Due to the complexity of the case, multidisciplinary management was necessary. Further studies of this type of patients are needed.